Phage display as a tool for development of novel therapeutics for breast cancer - Cabral, Maria Jardim Caramelo Dias (2014)
Phage display technology is a powerful platform for the generation of highly specific human monoclonal antibodies (Abs) with potential use in clinical applications. Moreover, this technique has also proven to be a reliable approach in identifying and validating new cancer-related targets. For scientific or medical applications, different types of Ab libraries can be constructed. The use of Fab Immune libraries allows the production of high quality and affinity antigen-specific Abs. In this work, two immune human phage display IgG Fab libraries were generated from the Ab repertoire of 16 breast cancer patients, in order to obtain a tool for the development of new therapeutic Abs for breast cancer, a condition that has great impact worldwide. The generated libraries are estimated to contain more than 108 independent clones and a diversity over 90%. Libraries validation was pursued by selection against BSA, a foreign and highly immunogenic protein, and HER2, a well established cancer target. Preliminary results suggested that phage pools with affinity for these antigens were selected and enriched. Individual clones were isolated, however, it was not possible to obtain enough data to further characterize them. Selection against the DLL1 protein was also performed, once it is a known ligand of the Notch pathway, whose deregulation is associated to breast cancer, making it an interesting target for the generation of function-blocking Abs. Selection resulted in the isolation of a clone with low affinity and Fab expression levels. The validation process was not completed and further effort will have to be put in this task in the future. Although immune libraries concept implies limited applicability, the library reported here has a wide range of use possibilities, since it was not restrained to a single antigen but instead thought to be used against any breast cancer associated target, thus being a valuable tool.